PENERAPAN MEDIA PASIR UNTUK MENINGKATKAN KEMAMPUAN MENULIS PADA KELOMPOK A PAUD - Sry Anita Rachman; Laily Fitriani (JURNAL ASIMILASI PENDIDIKAN, 2024)
Early childhood education is the most basic education and is referred to as the golden period or what is known as the golden age. This research aims to investigate and understand the effect of using sand media as a learning tool on early writing abilities in early childhood. This research uses a classroom action research method with data collection techniques through observation and interviews. Analysis techniques through data collection, data reduction and drawing conclusions. The results of this research show that the application of sand media provides a unique learning experience for students that allows children to feel the text and letter shapes. Apart from that, this media can also be a variety of alternative media in teaching children to learn to write.